Pengaruh Inokulasi Cendawan Mikoriza Arbuskular (CMA) dan Pemupukan Fosfat terhadap Pertumbuhan dan Produksi Tanaman Kedelai (Glycine max (L.) Merrill) - Ika Fatikah; Dwi Retno Lukiwati; Budi Adi Kristanto (Journal of Agro Complex, 2018)
The objective of this research was to study the growth and production of soybean at various doses of inoculum arbuscular mycorrhizal fungi (AMF) and phosphate fertilization i.e. guano, rock phosphate, guano+rock phosphate and TSP. This research was conducted in green house and Laboratory of Plant Physiology and Breeding, Faculty of Animal and Agricultural Sciences, Diponegoro University, and Laboratory of Micology, Gadjah Mada Universityfrom April 16th to August 18th 2017. The research was assigned in completely randomized factorial design with the first factor was the doses of inoculum AMF (0, 30, 45 and 60g/pot) and second factor was the phosphate fertilization (control, guano, rock phosphate, guano+rock phosphate and TSP). The results showed that inoculation of AMF with doses of 30 and 45 g/pot had significant effect on plant height, number of branches and pods. Inoculation of AMF with a dose of 60 g/pot significantly affected the number of branches and pods. Fertilization of guano, BP and guano+BP had significant effect on number of branches and pods, TSP fertilization had significant effect on plant height, number of branches and pods. Keyword: soybean, arbuscular mycorrhizal fungi, phosphorus fertilization